Elastin-Like Polypeptide: VEGF-B Fusion Protein for Treatment of Preeclampsia. Issue 6 (December 2021) - Waller, Jamarius P.; Howell, John Aaron; Peterson, Hali; George, Eric M.; Bidwell, Gene L.
Abstract : Preeclampsia is characterized by the development of elevated blood pressure during the second and third trimesters of pregnancy that is accompanied by end organ dysfunction. The pathogenesis of preeclampsia is multifactorial but is commonly characterized by endothelial dysfunction and the overproduction of antiangiogenic factors, including the soluble VEGF (vascular endothelial growth factor) receptor sFlt-1 (soluble Fms-like tyrosine kinase receptor 1). Previously, administration of exogenous VEGF-A, bound to a carrier protein called ELP (elastin-like polypeptide), significantly reduced free sFlt-1 levels and attenuated the hypertensive response in a rodent model of preeclampsia. However, VEGF-A administration induces multifactorial effects mediated through its direct activation of the Flk-1 receptor. In response to this, we developed a therapeutic chimera using ELP bound to VEGF-B, a VEGF isoform that binds to sFlt-1 but not to Flk-1. The purpose of this study was to evaluate the in vitro activity and pharmacological properties of ELP-VEGF-B and to test its efficacy in the reduced uterine perfusion pressure rat model of placental ischemia. ELP-VEGF-B was less potent than ELP-VEGF-A in stimulation of endothelial cell proliferation and matrix invasion, indicating that it is a weaker angiogenic driver. However, after repeated subcutaneous administration in pregnant rats, ELP-VEGF-B was maternally sequestered and reduced blood pressure when compared with saline treated animals following induction of placental ischemia (123.38±11.4 versus 139.98±10.56 mm Hg, P =0.0129). Blood pressure reduction was associated with a restoration of the angiogenic capacity of plasma from rats treated with ELP-VEGF-B. ELP-VEGF-B is a nonangiogenic, maternally sequestered protein with potential efficacy for treatment of preeclampsia. Abstract : Supplemental Digital Content is available in the text.